2018
DOI: 10.1002/ecs2.2435
|View full text |Cite|
|
Sign up to set email alerts
|

Restoration increases bee abundance and richness but not pollination in remnant and post‐agricultural woodlands

Abstract: Human land use, including agriculture, is a leading contributor to declining biodiversity worldwide and can leave long‐lasting legacies on ecosystems after cessation. Ecological restoration is an approach to mitigate these impacts. However, little is known about how animal communities and plant–animal interactions respond to the combined effects of land‐use legacies and restoration. We investigated how restoration and agricultural history affect bee (Hymenoptera: Apoidea: Anthophila) communities and pollinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 71 publications
3
23
0
Order By: Relevance
“…Large‐bodied species may be more affected by land use, but they are also able to fly long distances between patches and so larger experimental plots would be needed to test effects on these bees. A related study incorporating net collections across additional sites suggests the patterns observed here are maintained over multiple years and also apply to a wider range of bee species (Breland et al ). Although land‐use history did not appear important for bee diversity in this study, it may play a stronger role in other species with stronger dependencies on specific floral hosts.…”
Section: Discussionmentioning
confidence: 60%
“…Large‐bodied species may be more affected by land use, but they are also able to fly long distances between patches and so larger experimental plots would be needed to test effects on these bees. A related study incorporating net collections across additional sites suggests the patterns observed here are maintained over multiple years and also apply to a wider range of bee species (Breland et al ). Although land‐use history did not appear important for bee diversity in this study, it may play a stronger role in other species with stronger dependencies on specific floral hosts.…”
Section: Discussionmentioning
confidence: 60%
“…Thinning creates canopy gaps, which changes understorey microclimate and vegetation (Ares, Neill, & Puettmann, 2010;Nunes, Oliveira, Cabral, Branquinho, & Correia, 2014;Son, Lee, Jun, & Kim, 2004) and has been known to increase abundance and/or diversity of bees in other forests (Proctor, Burke, & Crins, 2012;Taki et al, 2010). Furthermore, another study that thinned longleaf pine forests close to our study region saw increased bee abundance and richness (Breland et al, 2018).…”
Section: Plantation Thinningmentioning
confidence: 63%
“…Thinning may lead to increases in biodiversity. A study conducted in a U.S. national forest in Georgia observed greater bee species richness in thinned compared to dense pine forests (Hanula, Horn, & O'Brien, 2015; but see Breland, Turley, Gibbs, Isaacs, & Brudvig, 2018). Fallen woody debris is another by-product of timber production that may be harvested for biomass (Riffell, Verschuyl, Miller, & Wigley, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Common garden experiments have identified candidate species for such efforts (Tuell et al, 2008;Rowe et al, 2018). Likewise, restoration management, such as thinning and burning, will often alter total pollinator abundances, community composition, and richness, sometimes negatively (Potts et al, 2003;Breland et al, 2018), in part by affecting nest sites and influencing floral resource availability (Potts et al, 2003;National Research Council of the National Academies, 2007). As a result, the scale at which disturbances are applied should be carefully considered to allow refuges for pollinators and other taxa (Shuey, 2013).…”
Section: Fire Mowing and Promoting Pollinatorsmentioning
confidence: 99%